Principles and practices of biophilia: is the human-nature connection possible for the municipality of Santo André, SP? - Melo, Sheyla Regiane de; Toledo , Renata Ferraz de (Technical and Scientific Journal Green Cities, 2025)
Objective – to investigate the principles and practices of biophilia and sustainability urbanism, analyzing their potential and challenges applicable to the urban planning of Santo André, São Paulo. Methodology – A qualitative case study was conducted using a narrative literature review, document analysis, and map production using the Andreense Geographic Information System (SIGA), which were analyzed interpretatively and critically. Originality/Relevance – The research updates and expands the production of theoretical and methodological knowledge on biophilia, bringing together guiding principles, practical examples of its application in urban contexts, and also analyzes possibilities of its adoption in the municipality of Santo André, São Paulo. Results – The municipality of Santo André, due to its spatial and socio-environmental characteristics and its Goals Plan, demonstrates potential for adopting principles and practices of biophilia and sustainable urbanism. To this end, it is essential to incorporate these premises into its urban planning, dialogue with society, and environmental education processes. Theoretical/Methodological Contributions – Theoretical foundation of biophilia and biophilic cities, based on Timothy Beatley, and the human-nature relationship in urban space, based on Cecília Polacow Herzog, as well as methodological contributions adopted in this research, in an integrated manner, as a case study, through bibliographic review, documentary research and map production bring relevant contributions to the interface of the areas of urbanism, environment and health. Social and Environmental Contributions – It is considered that biophilic urbanism, when planned and executed, beyond wooded areas concentrated in parks and squares, redefines coexistence and permanence in other public spaces, reaching anthropic means such as paving, public transportation, schools and public services, providing a broader understanding of this human-nature relationship and better road quality.